Delimiting species within the Lysmata vittata (Stimpson, 1860) (Decapoda: Lysmatidae) species complex in a world full of invaders - Guéron, Rodrigo; Almeida, Alexandre Oliveira; Aguilar, Robert; Ogburn, Matthew B.; Prakash, Sanjeevi; Baeza, J. Antonio (Zootaxa, 2022)
Historically, Lysmata vittata has been reported with a near global non-polar distribution. Early studies reported a wide morphological variation in this species, which served as a basis for further synonymization of at least four species. Herein, we investigated the species diversity within L. vittata complex and tested whether L. rauli and L. durbanensis are valid species instead of junior synonyms of L. vittata. Our integrated morphological and molecular data strongly supports the validity of at least six taxonomic entities within the broader L. vittata complex, including L. rauli and L. durbanensis and three undescribed species. Multivariate analyses highlighted prominent morphological differences in accessory branch structure of dorsolateral antennular flagellum, number of carpal and meral segments of the second pereopod, and color pattern which segregated shrimps into distinct morpho-groups. Phylogenetic analyses supported morphological groupings and recovered five widely divergent lineages, which corresponded to the morphological groupings: L. vittata sensu stricto; L. rauli sensu stricto; L. sp. CHINA; L. sp. AUS1; and L. sp. AUS2. Therefore, we formally resurrect L. rauli to valid species status and posit it is native to the subtropical and tropical Indo West-Pacific. Although data were limited, we also formally resurrect L. durbanensis to valid species status from southern Africa. Our results imply L. vittata and L. rauli are exotic species in the western Atlantic, New Zealand, and the Mediterranean. This study provides a solid framework to continue untangling the historic L. vittata species complex, which is likely to include additional species to the ones included in the present study.